Arterial Spin Labeling and Dynamic Susceptibility Contrast-Enhanced Perfusion MRI in Evaluation of Adult Patients with Gliomas - N. I. Eltatawy, Dawlat; Elsharawy, Fatma A.; A. Khodair, Sameh; S. Mahmoud, Hanan; El-Ahwal, Hanan M. S. (Journal of Neonatal Surgery, 2025)
Objectives: To highlight the role of ASL and DSC perfusion MRI in the diagnosis, grading, and follow-up of adult patients with gliomas. Methods: This prospective study was carried out on 40 patients with MRI features of glioma either for grading or for follow up ,aged from 19 to 68 years old. Non-contrast ASL followed by DSC-PI was done for all cases. The final diagnosis of the cases was established by histopathology. Results: There was a highly strong correlation between absolute ASL- tumoral cerebral blood flow (tCBF) and absolute DSC -tCBF and DSC-cerebral blood volume (tCBV). ASL- tCBF was significantly different between IDH multiform (GBM) and IDH multiforme (GBM) residual after radiotherapy and chemotherapy. Both ASL and DSCE qualitative color maps showed significant difference between low and high glioma grades. Both ASL-tCBF and ASL –rCBF had sensitivity of 91.9% ,specificity of 90.9 % ,PPV of 91.9% and NPV of 91.9% . DSC-tCBV had sensitivity of 91.6%, specificity of 81.8%, PPV of 84.6% and NPV of 90%. Conclusions: ASL can serve as a good alternative for dynamic contrast-enhanced perfusion MRI in preoperative grading as well as in follow up of gliomas.